Valery Bryusov about the poetry of the French poet-symbolist Paul Verlaine on the pages of the «Vesy» magazine - Oganesyan K. A. (Interactive science, 2017)
the article describes the Valery Bryusov’s activity in «Vesy» magazine as a translator and critic of the French poet-symbolist Paul Verlaine. Paul Verlaine’s poetry has had an important impact on the Russian symbolism development.
Keywords: символизм; symbolism; Валерий Яковлевич Брюсов; французская поэзия; Верлен; журнал «Весы»; Valery Yakovlevich Bryusov; French poetry; Verlaine; «Vesy» magazine